Payment for environmental services to reduce deforestation: Do the positive effects last? - Kemigisha, E.; Babweteera, F.; Mugisha, J.; Angelsen, A. (Elsevier, 2023)
Are the forest conservation practices sustained after Payment for Environmental Services (PES) programmes end? Using a sample of 268 (former) PES recipients and non-recipients from the Budongo-Bugoma PES programme in Western Uganda, we employ the before-after-control–intervention (difference-in-difference) approach to estimate the PES programme outcome on their privately owned forests. PES is associated with less deforestation during the operational period, but the link has vanished four years after programme termination. We label this weak permanence, i.e., PES recipients abandon the induced practices soon after the programme ended, but the gains (relatively higher forest cover) during the operational period are maintained. We also find that household and contextual variables are important in explaining PES permanence: low levels of agricultural land and remoteness from agricultural markets weaken PES permanence. Therefore monetary payments alone may be insufficient for lasting forest conservation. Integrating PES with other approaches, such as climate-smart agriculture may result in more permanent reductions in deforestation.